From Stress to Support: How Technostress Inhibitors Drive Task Productivity in Public Institutions - Şahan, Esra; Demirel, Hatice Gökçe (My University, 2025)
Purpose: The purpose of this study is to examine the effects of technostress creating factors (creators) and inhibitors on the task productivity of employees. Method: In this study, the survey method, one of the quantitative research techniques, was used. The field application was conducted on academic and administrative staff of Fırat University (Elazıg). A total of 356 surveys suitable for data analysis were obtained. The data were analyzed in the SPSS statistics program. Findings: According to the regression analysis findings, the effect of technostress creators on task productivity is statistically non-significant, and technostress creators explain only 2% of the variance in task productivity. However, it was observed that techno-uncertainty, which is one of the factors contributing to technostress, had a significant effect. The effect of technostress inhibitors on task productivity was significant and explained 21% of the variance. It has also been found that job satisfaction had the highest effect among technostress inhibitors and continuance commitment did not have a significant effect. Originality: Studies in the literature mainly focus on the effects of technostress creators and inhibitors on motivation, burnout, productivity and performance. Our research examines the effects of technostress creators and inhibitors on task productivity.
Keywords: Digitalization; Organizational Behavior; Technology Management; Technostress; Task Productivity